Screening the antagonistic activity of beneficial bacteria against the pathogen of fruitlet core rot disease on pineapple / Tuan Nurul Hayati Tuan Lah - Tuan Lah, Tuan Nurul Hayati (Faculty of Plantation and Agrotechnology, 2019)
Fruitlet core rot (FCR) caused by Penicillium sp. is one of the major diseases that affecting pineapple production. FCR attacks pineapple fruit and caused low quality and quantity of fruit for market. The first objective of this study was to isolate and confirm the causal pathogen of FCR through Koch‟s postulate. The second objective was to isolate beneficial bacteria from healthy pineapple fruitlet of MD2 variety and screen their antagonistic activity against the FCR pathogen. A dual culture method was used to identify the antagonistic activity of beneficial bacteria against the pathogen. In this study, nine beneficial bacteria isolates coded as B1, B2, B3, B4, B5, B6, B7, B8 and B9 were isolated to access their potential as biological control agent for FCR pathogen. The highest percentage of mycelial inhibition growth rate for bacteria microbe isolates named B2 and B9 with values of 91.67% and 96.83%, respectively. The data retrieved from percentage of inhibition of radial growth (PIRG) were analyzed by using One-way ANOVA using SPSS version 22. The top nine antagonistic bacteria were identified based on under microscope. Then, infected fruit was show the symptom externally and in-ternally. Severely affected fruitlets may turn brown and sunken as the fruit ripens. Then, the internal part of the fruit consists of a browning of the center of fruitlets starting below the floral cavity and sometimes extending to the core. So, Koch‟s postulate was show the positive symptoms that could prove the FCR disease can caused by Penicillium sp.